Self-seeded FEL wavelength extension with high-gain harmonic generation - 曾凌 秦伟伦 赵刚 黄森林 Yuantao Ding Zhirong Huang Gabriel Marcus 刘克新 (Chinese physics C, 2016)
We study a self-seeded high-gain harmonic generation（HGHG） free-electron laser（FEL） scheme to extend the wavelength of a soft X-ray FEL. This scheme uses a regular self-seeding monochromator to generate a seed laser at the wavelength of 1.52 nm, followed by a HGHG configuration to produce coherent, narrow-bandwidth harmonic radiations at the GW level. The 2nd and 3rd harmonic radiation is investigated with start-to-end simulations.Detailed studies of the FEL performance and shot-to-shot fluctuations are presented.